The Leeds hand transplant programme: Review of the laboratory management of the first six cases. (15th December 2019) - Clark, Brendan; Carter, Clive; Wilks, Daniel J.; Lobb, Mark; Hughes, Pamela; Baker, Richard; Kay, Simon P. J.
Abstract: The UK hand transplantation programme is hosted by the Department of Plastic and Reconstructive Surgery at Leeds Teaching Hospitals under the leadership of Professor Simon Kay. Since programme launch in 2013, ten procedures in six individuals have been performed involving unilateral or bilateral transplants. The multi‐disciplinary team that delivers the programme includes the transplant immunology service. The laboratory experience in programme support is reported here.